Alternative therapies for the management of inhibitors. (July 2016) - Shima, M.; Lillicrap, D.; Kruse‐Jarres, R.
Abstract : The development of inhibitors to factor VIII (FVIII) or factor IX (FIX) remains a major treatment complication encountered in the treatment of haemophilia. Not all patients with even the same severity and genotype develop inhibitors suggesting an underlying mechanism of tolerance against FVIII‐ or FIX‐related immunity. One mechanism may be central tolerance observed in patients in whom the FVIII mutation enables some production of the protein. The other is a peripheral tolerance mechanism which may be evident in patients with null mutation. Recently, recombinant porcine FVIII (rpFVIII, Obixur, OBI‐1, BAX801) has been developed for the haemostatic treatment of both congenital haemophilia with inhibitor (CHAWI) and acquired haemophilia A (AHA). In 28 subjects with AHA with life‐/limb‐threatening bleeding, rpFVIII reduced or stopped bleeding in all patients within 24 h. The cross‐reactivity of anti‐human FVIII antibodies to rpFVIII remains around 30–50%. Recently, new therapeutics based on the quite novel concepts have been developed and clinical studies are ongoing. These are humanized asymmetric antibody mimicking FVIIIa function by maintaining a suitable interaction between FIXa and FX (Emicizumab, ACE910), and small interfering RNAs (siRNA, ALN‐AT3) suppress liver production of AT through post‐transcriptional gene silencing and a humanized anti‐TFPI monoclonal antibody (Concizumab). Their main advantages are longer half‐life, subcutaneous applicability and efficacy irrespective of the presence of inhibitors which will make it easier to initiate more effective treatment especially early childhood.